Causes of mortality in elderly UICC stage III colon cancer (CC) patients––Tumor‐related death and competing risks from the German AIO colorectal study group Colopredict Plus (CPP) registry. (11th February 2022) - Nöpel‐Dünnebacke, Stefanie; Jütte, Hendrick; Denz, Robin; Feder, Inke Sabine; Kraeft, Anna‐Lena; Lugnier, Celine; Teschendorf, Christian; Collette, Daniela; Böhner, Hinrich; Engel, Lars; Mueller, Lothar; Hartmann, Frank; et al.
Abstract: Background: Colon cancer (CC) is a disease of elderly patients (pts.) with a median age of 73 years (yrs.). Lack of data about the effects of adjuvant chemotherapy (ACT) is caused by underrepresentation of this clinically relevant cohort in interventional trials. We analyzed real‐world data from the German CPP registry with regard to a possible benefit of ACT in elderly (70+ yrs.) versus younger pts. (50 to <70 yrs.) taking cause‐specific deaths into account. Methods: We analyzed the effect of age and ACT on overall survival (OS) and cause‐specific death of stage III pts. using Cox regression. Results: In total, 1558 pts. were analyzed and follow‐up was 24.6 months. 62.6% of the elderly received ACT whereas 91.1% of younger pts. ( p  < 0.001). Oxaliplatin combinations were significantly less often given to older than younger pts. (38.8% vs. 88.9%; p  < 0.001). Mean Charlson comorbidity score was significantly lower in pts. that received ACT (0.61) than in those without ACT (1.16; p  < 0.001). ACT was an independent positive prognostic factor for cancer‐related death in elderly pts. even in pts. 75+ yrs. No significant difference in the effect of ACT could be observed between age groups (interaction: cancer‐specific death HR = 1.7948, p  = 0.1079; death of other cause HR = 0.7384, p  = 0.6705). Conclusion: ACT was an independent positive prognostic factor for OS. There may be a cohort of elderly with less co‐morbidities who benefit from ACT. Abstract : More than half of CC cases are diagnosed in patients aged over 70 years who form a particularly heterogeneous cohort regarding functional status, comorbidities, and social support. Guidance in cancer‐treatment decisions is complicated by a lack of high‐quality evidence. Our analysis evaluated the impact of ACT on survival and causes of death in elderly with CC within the real‐world AIO registry CPP. ACT was an independent positive prognostic factor for cancer‐related death; OS and DFS were significantly higher in pts. who received ACT. These data implicate that elderly with few comorbidities eligible to receive ACT, might benefit like their younger counterparts